What Determines the Selection of Public Accounting Firms? Case of Listed Mining Companies in Indonesia - Mahfud Mahfud; Mirna Indriani; Indayani Indayani (Journal of Accounting Research, Organization and Economics, 2020)
Objective – This study aims to determine the effect of institutional ownership, managerial ownership, board size and debt on the selection of public accounting firms in mining sector companies listed on the Indonesia Stock Exchange (IDX).  Design/methodology – This study uses big four and non-big four public accounting firms classification as a proxy of the quality of the firm that will be selected by the company. It utilizes 120 observations during the 2015-2017 period. The analysis technique used is logistic regression.  Results – The results showed that the size of the board of commissioners affected the election of qualified public accountant. While institutional ownership, managerial and debt holdings have no effect on the selection of qualified public accounting firms.